Adsorption properties of n-octane/1-octene binary mixtures in the zeolitic imidazolate frameworks, ZIF-8 and ZIF-67: Combined experimental and molecular simulation study - Jo, Sungbin; Kim, Jayeon; Jung, Taesung; Cho, Dong Woo; Yoo, Chung Yul (Microporous and Mesoporous Materials, 2024)
1-Octene, a linear α-olefin, can be used as a comonomer for producing plastics, oils, waxes, and surfactants. High-purity 1-octene can be obtained by removing paraffin byproducts using energy-intensive distillation. Adsorptive separation using porous material–based adsorbents is a promising alternative to distillation. Most reported adsorbents are zeolites, which preferentially adsorb 1-octene rather than n-octane owing to their polar framework. However, the existing studies are insufficient for investigating apolar adsorbents that adsorb more amounts of n-octane than 1-octene. Herein, the adsorption properties of the apolar adsorbents, zeolitic imidazolate frameworks-8 (ZIF-8) and ZIF-67, obtained from a n-octane/1-octene liquid binary mixture were systematically investigated by conducting batch adsorption experiments for the n-octane volume fraction of 10 %–90 %. Results show that ZIF-8 and ZIF-67 are promising adsorbents for the selective adsorption of n-octane owing to the preferential adsorption of n-octane in the micropores of the ZIFs at the high concentration of n-octane. Configurational-bias grand canonical Monte Carlo simulations confirm that the host–adsorbate energy between ZIF-8 and n-octane is higher than that between ZIF-8 and 1-octene, whereas the host–adsorbate energy between ZIF-67 and n-octane is similar to that between ZIF-67 and 1-octene.
Keywords: 1-octene; Adsorption properties; Energy; Grand canonical Monte Carlo simulation; Imidazol; Linear α-olefins; Liquid binary mixtures; N-octanes; Zeolitic imidazolate framework-8; Zeolitic imidazole framework; Adsorbent; Grand canonical Monte Carlo simulation; Linear α-olefin; Liquid binary mixture; Zeolitic imidazole framework